APPLICATION OF 5S PROGRAM TO IMPROVE FABRIC STOCK MANAGEMENT IN MANUFACTURING INDUSTRY - LIMA, MARCO ANTONIO XAVIER DE; GALAN, CRISLAINE RODRIGUES; CASTILHO, ANA CAROLINA BRITTO; OLIVEIRA, EDUARDO ALVES DE (Uningá Review, 2018)
The aim of the present study was to implement the quality program 5S to improve the system of stock management in a manufacturing company in the northwest of Paraná. The maintenance of stocks involves a significant cost; for this reason, proper management is indispensable to avoid failures and pauses in the productive process due to lack of material. Thus, planning and controlling of stock are necessary to conciliate demand and supply of feedstock to provide constant production. In the studied manufacturing company, a painstaking management is required since for every new collection (every four months) a change on feedstock occurs, according to fashion trends of each season. Therefore, this study aims to improve the stock management by implementing the quality program 5S. After the implementation, it was possible to achieve the estimated results with rationalization of time, optimization of space, stock organization and reliability, a clean work environment and self-discipline of workers. As a result, the company became a pleasant, healthy and better place to work in.